Relapse prevention therapy for internet gaming disorder in Swedish child and adolescent psychiatric clinics: a randomized controlled trial - André, Frida; Kapetanovic, Sabina; Einarsson, Isak; Trebbin Harvard, Sunna; Franzén, Leonard; Möttus, Annika; Håkansson, Anders; Claesdotter-Knutsson, Emma (Frontiers in Psychiatry, 2023)
Objectives To evaluate the effectiveness of relapse prevention (RP) as a treatment for internet gaming disorder (IGD). Design Randomized controlled trial. Setting Three child and adolescent psychiatry (CAP) units in Region Skåne, Sweden. Participants Children aged 13–18 years, coming for their first visit to CAP during 2022, were screened for gaming behavior. Those who met the proposed DSM-5 criteria for IGD were offered participation in the trial, if they had the capacity to provide written informed consent and if they spoke Swedish. A total of 111 CAP patients agreed to participate. Out of those, 11 patients were excluded due to incorrect inclusion such as young age (n = 1), or due to the absence of responses to follow-up measures (n = 9). After exclusion, 102 participants remained (intervention = 47, control = 55). Interventions The intervention, RP, is based on cognitive behavioral treatment (CBT) and was provided individually, comprising of five to seven 45-min sessions over a period of 5 to 7 weeks versus treatment as usual. Outcome measures Participants were assessed with Game Addiction Scale for Adolescents pre-treatment (GASA) (baseline), post-treatment (treatment group only), and 3 months after baseline (follow-up). Results The repeated measures ANOVA showed a significant interaction effect between treatment and time. Both the control group and treatment group lowered their mean GASA score from baseline to follow-up significantly, but the improvement was greater in the treatment group (mean difference in control group −5.1, p < 0.001, 95% CI = − 3.390 to −6.755, mean difference in treatment group −9.9, p < 0.001, 95% CI = −11.746 to −8.105). Conclusion RP was found to be superior to treatment as usual in terms of reduction of IGD symptoms. Future research should address which aspects within a given treatment are effective, who benefits from treatment, in what aspects, and why. Trial registration number ClinicalTrials.gov, NCT05506384 https://clinicaltrials.gov/ct2/show/NCT05506384.